2014
DOI: 10.1007/s10548-014-0412-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Source Imaging in Posterior Cortex Epilepsies

Abstract: Posterior cortex epilepsies (PCE) are characterized by less satisfying postoperative results than temporal lobe epilepsies and are thus challenging for non-invasive presurgical investigations. The objective of this study was to evaluate the performance of magnetic source imaging (MSI) in PCE, validating the results by the SEEG (stereoelectroencephalography) definition of irritative and epileptogenic zones (IZ and EZ). Fourteen PCE surgery candidates were investigated using MSI and SEEG. LCMV (Linearly Constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 39 publications
2
8
0
1
Order By: Relevance
“…This kind of network distribution of spiking activity has also been observed in extratemporal epilepsies (Fig. ) …”
Section: The Epileptic Brain Shows Altered Functional Connectivity Dusupporting
confidence: 68%
See 1 more Smart Citation
“…This kind of network distribution of spiking activity has also been observed in extratemporal epilepsies (Fig. ) …”
Section: The Epileptic Brain Shows Altered Functional Connectivity Dusupporting
confidence: 68%
“…S1). 111 A study using the mean phase coherence algorithm revealed that areas of elevated local synchrony overlap with the EZ, suggesting that high local synchrony may be a marker for epileptogenic cortex. 112 Furthermore, this study suggested correlation between the resection of area of high local synchrony and good surgical outcome.…”
Section: The Epileptic Brain Shows Altered Functional Connectivity Dumentioning
confidence: 99%
“…Therefore, iEEG is only an incomplete gold standard as iEEG/MEG correlations is only valid within a close neighbourhood of each electrode contact. Correlations between MEG sources and invasive recordings has been mainly investigated using ECoG data [Agirre‐Arrizubieta et al, ; de Gooijer‐van de Groep et al, ; Fujiwara et al, ; Knowlton et al, ; Leijten et al, ; Mikuni et al, ; Minassian et al, ; Oishi et al, ; Tanaka et al, ], whereas some studies reported the comparison between MEG sources and iEEG recordings [Badier et al, ; Bouet et al, ; Gavaret et al, ; Jung et al, ; Schwartz et al, ], including our previous study reported in Heers et al []. Most of them consisted in qualitative description of the results, i.e., inference of sublobar accuracy between the two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them consisted in qualitative description of the results, i.e., inference of sublobar accuracy between the two techniques. Whereas quantitative detection of the irritative and epileptogenic zone from iEEG data was provided in Badier et al [], the correlation with MEG sources remained qualitative and at a sublobar level. In this study and as a continuation of our previous qualitative evaluation [Heers et al, ], we proposed a quantitative approach to compare iEEG/MEG data taking into account the limited spatial sampling of iEEG data.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the irritative zone is larger than the seizure onset zone (Talairach and Bancaud, 1966) and may form a distinct network independent from the seizure onset zone (Bourien et al, 2005). These regions represent the 'secondary irritative zone' and are generally regions affected by seizure propagation (Badier & Chauvel 1995;Badier et al 2014;Bettus et al 2010). Finally, even in intracranial EEG, concordance between the areas generating interictal spikes and those generating seizures is good for only about 60 % of patients (75% with focal cortical dysplasia) (Bartolomei et al, 2016).…”
Section: Intracerebral Organization Of Interictal Spikesmentioning
confidence: 99%